Determinants of Low birth Weight in Durame General Hospital Ethiopia 2016 ,case control study - Tembiso, Simegn Alemu (PONS - medicinski časopis, 2018)
Abstract Background: Low birth weight plays an important role in infant mortality and morbidity of the child. Weight at birth is directly influenced by general status of the mother, but, little is known about what determines being low birth weight among neonates. Therefore, this study is aimed to assess the determinants of low birth weight among neonates in health facilities of Kambata Tembaro Zone, SNNP Ethiopia. Methods: Institution-based case control study was conducted. Neonates born with birth weight less than 2500 gm were grouped into cases and those neonates with weight greater or equal to 2500 were grouped as Controls. A total of 282 participants (57 cases and 225 Controls) were included with controls to cases ratio of 4:1.Data were entered using Epi data version 3.1 and exported to SPSS version 20 for analysis. Binary logistic regression was done to get candidate variables. Adjusted odd ratio was estimated from multiple logistic analysis with corresponding confidence interval to assess strength of association and statistical significance between independent and outcome variable.    Results: A total of 282 neonates (57 cases and 225 controls) comprised the study participants. The mean birth weight of the neonates was 2041.23 gm. (S.D± 339.001) for Cases and 376.00gm (S.D± 438.572) for Controls. Among mothers of neonates 38 (66.7%) cases’ and 146(64.9%) controls’ were age > 24years old. and 40(70.2%) cases’ and 164(72.9 %) controls’ were living in rural area. Majority 44 (77.2%) of mothers of cases’ and 180 (80%) controls ‘were housewives. Household food in-security (AOR= 6.74; 95% CI(2.78-16.36).Sex of neonates being female (AOR=2.74;95%CI(1.24-6.05) Iron supplementation (AOR=9.71;95%CI(3.51-26.88), additional food during pregnancy_(AOR=5.49 ;95%CI (2.49,12.11) and anemia AOR=3.51;95%CI(1.56-7.85) were significantly associated with LBW at term. Conclusion and Recommendation: Low birth weight was associated with iron folate, Additional diet during pregnancy, Household food in-security and anemia of the mother. Therefore, the key elements of antenatal care such as iron intake and dietary advice which are likely to improve low birth weight. Improving mother’s food insecurity status also plays important role in decreasing Low birth weight.